2004
DOI: 10.1056/nejmoa041318
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel and Estramustine Compared with Mitoxantrone and Prednisone for Advanced Refractory Prostate Cancer

Abstract: The improvement in median survival of nearly two months with docetaxel and estramustine, as compared with mitoxantrone and prednisone, provides support for this approach in men with metastatic, androgen-independent prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

57
2,271
6
73

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 3,358 publications
(2,407 citation statements)
references
References 19 publications
57
2,271
6
73
Order By: Relevance
“…3 Unfortunately, in virtually all patients, the disease inevitably advances to the androgen-independent stage within a median of 18-24 months after castration. 4 Two randomized phase III studies, SWOG 99-16 4 and TAX 327, 5 demonstrated that docetaxel-based chemotherapy confers a significant survival benefit of 20%-24% in patients with metastatic castration-resistant prostate cancer (mCRPC) compared with a mitoxantrone regimen. 6 Nevertheless, many patients failed to respond to docetaxel chemotherapy and experienced considerable toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…3 Unfortunately, in virtually all patients, the disease inevitably advances to the androgen-independent stage within a median of 18-24 months after castration. 4 Two randomized phase III studies, SWOG 99-16 4 and TAX 327, 5 demonstrated that docetaxel-based chemotherapy confers a significant survival benefit of 20%-24% in patients with metastatic castration-resistant prostate cancer (mCRPC) compared with a mitoxantrone regimen. 6 Nevertheless, many patients failed to respond to docetaxel chemotherapy and experienced considerable toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Androgen withdrawal is an effective therapy for patients with advanced prostate cancer, but progression to hormone independence occurs ultimately in almost all patients after a few months or years (Petrylak et al, 2004). Although numerous non-hormonal agents have been evaluated in patients with hormone-refractory prostate cancer, these agents have limited antitumor activity with modest or no effect on survival (Petrylak et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Of the seven RCTs included, three used docetaxel compared with mitoxantrone plus prednisone (Petrylak et al, 2004;Tannock et al, 2004;Oudard et al, 2005), three used mitoxantrone plus a corticosteroid compared with a corticosteroid (used as active supportive care) (Tannock et al, 1996;Kantoff et al, 1999;Berry et al, 2002) and one used mitoxantrone plus prednisone compared with mitoxantrone plus prednisone plus clodronate (Ernst et al, 2003). There were no trials comparing docetaxel plus prednisolone/prednisone or mitoxantrone plus a corticosteroid with other Figure 1 Process of study selection.…”
Section: Resultsmentioning
confidence: 99%
“…We found three RCTs comparing mitoxantrone plus prednisone with another chemotherapy regimen: one small RCT compared mitoxantrone plus prednisone with 3-weekly docetaxel plus prednisone plus estramustine and docetaxel twice every 3 weeks plus prednisone plus estramustine in 130 men with mHRPC (Oudard et al, 2005); one RCT compared mitoxantrone plus prednisone with 3-weekly docetaxel plus estramustine in 770 men with mHRPC (Petrylak et al, 2004); and one double-blind RCT compared mitoxantrone plus prednisone plus placebo with mitoxantrone plus prednisone plus clodronate in 227 men with mHRPC and stable levels of analgesic use (Ernst et al, 2003). Overall survival and progression-free survival were statistically significantly improved with docetaxel plus estramustine compared with mitoxantrone plus prednisone, response rate was statistically significantly improved with docetaxel plus prednisone plus estramustine compared with mitoxantrone plus prednisone and PSA decline was statistically significantly improved for both regimens containing docetaxel compared with mitoxantrone plus prednisone.…”
Section: Control (N ¼ 123): Hydrocortisone (As Above)mentioning
confidence: 99%